1985
DOI: 10.1099/00221287-131-6-1383
|View full text |Cite
|
Sign up to set email alerts
|

Cytolytic and Phospholipase C Activity in Legionella Species

Abstract: To examine one possible mechanism of damage to leucocytes and tissue cells in legionellosis, seven species of Legionella were examined for cytolytic activity and for elaboration of phospholipase C, an enzyme that can damage mammalian cell membranes. Cytolysis was assessed using erythrocytes in agar. Phospholipase C was assayed by release of p-nitrophenol from p-nitrophenylphosphorylcholine and of tritiated phosphorylcholine from L-alpha-dipalmitoyl-[choline-methyl-3H]phosphatidylcholine. L. pneumophila, L. boz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
33
0
1

Year Published

1991
1991
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 38 publications
4
33
0
1
Order By: Relevance
“…The existence of both acid and alkaline phosphatases is known in legionellae (15,31). Next, we examined the hydrolysis of It is known that PLC, PLD, the combined action of PLA 1 and PLA 2 , or the collaboration of PLA and acyltransferase are each able to release tritiated water-soluble components such as 3 H-PrC, 3 H-choline, and 3 H-GPC from 3 H-PC, respectively. Since we could demonstrate that Legionella possesses PLA (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The existence of both acid and alkaline phosphatases is known in legionellae (15,31). Next, we examined the hydrolysis of It is known that PLC, PLD, the combined action of PLA 1 and PLA 2 , or the collaboration of PLA and acyltransferase are each able to release tritiated water-soluble components such as 3 H-PrC, 3 H-choline, and 3 H-GPC from 3 H-PC, respectively. Since we could demonstrate that Legionella possesses PLA (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The same strains hydrolyzed various amounts of p-NPPC; L. bozemanii exhibited the greatest activity. In decreasing quantity, L. pneumophila, L. dumoffii, L. jordanis, L. bozemanii, and L. longbeachae, but not L. micdadei, released a radioactive water-soluble product from 3 H-PC which was assumed to be 3 H-PrC. Baine concluded that five of the six Legionella species under investigation possessed PLC activity (3).…”
mentioning
confidence: 99%
“…The cytopathology of lungs infected by L. pneumophila suggests involvement of extracellular proteolytic enzymes or taxins in the pathogenesis of Legionella [2,18]. In order to select cloned toxin determinants of Legionella the recombinant E. coli K-12 clones were screened on blood agar plates containing human and canine erythrocytes.…”
Section: Expression Of Toxinsmentioning
confidence: 99%
“…For the determination of p-NPPC hydrolase, 100 l L. pneumophila culture supernatant or lysate (diluted at 1:2 with 40 mM Tris-HCl, pH 7.5, 25°C) were incubated with the same volume of substrate mixture containing 10 mM p-NPPC (Sigma-Aldrich, Taufkirchen, Germany), 6 mM NaN 3 , 1% (vol/vol) Triton X-100, and 10 mM MnCl 2 in 40 mM Tris-HCl (pH 7.5, 25°C) at 37°C and with continuous agitation at 100 to 170 rpm for 20 to 50 h. Subsequently the release of p-nitrophenol (p-NP) was measured optically at a wavelength of 405 nm and compared to p-NP (SigmaAldrich, Taufkirchen, Germany) standard solutions (9,22). BYE broth and 40 mM Tris-HCl, pH 7.5 (25°C), were used as negative controls.…”
Section: Methodsmentioning
confidence: 99%
“…L. pneumophila secretes a p-NPPC-hydrolyzing activity into its culture supernatant and the PlcA protein contributes to this activity (5,9,22). p-NPPC is an artificial substrate for phosphodiesterases, for example, phospholipases C, and has additionally been shown to be cleaved by phosphatases (22,23,66).…”
Section: Vol 188 2006 Control Of Hydrolytic Activities In L Pneumomentioning
confidence: 99%